2015
DOI: 10.1177/0218492315594071
|View full text |Cite
|
Sign up to set email alerts
|

Polyglycolic acid mesh occlusion for postoperative bronchopleural fistula

Abstract: Bronchoscopic occlusion with polyglycolic acid mesh with or without fibrin glue is easy and feasible as the first step in postoperative management of bronchopleural fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…However, despite multiple strategies reported and adequate risk-factor assessment (8)(9)(10), management of air leakage remains a major challenge. Furthermore, it is often associated with prolonged hospital stays, increased cost (11), and even empyemas (12). To avoid these complications, an appropriate stapling technique is required.…”
Section: Review Articlementioning
confidence: 99%
“…However, despite multiple strategies reported and adequate risk-factor assessment (8)(9)(10), management of air leakage remains a major challenge. Furthermore, it is often associated with prolonged hospital stays, increased cost (11), and even empyemas (12). To avoid these complications, an appropriate stapling technique is required.…”
Section: Review Articlementioning
confidence: 99%
“…[ 14 ] Moreover, previous reports have suggested that endobronchial treatment can be an optimal alternative treatment for postoperative BPF. [ 2 , 9 , 15 ] According to reports published after 2000, the overall success rate of endoscopic treatment ranges from 70% to 100%. [ 8 , 9 , 15 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…As reported previously, many bronchoscopic attempts to treat BPF have been described and include mechanical abrasion, vascular coils, fibrin or tissue glue, spigots, stents, silver nitrate, autologous endobronchial blood patches, and endobronchial valves. [ 2 , 6 , 9 , 15 19 ] In our case, because the fistula seemed to be relatively small, we did not use silicon spigots or vascular coils, which are likely to be effective for larger fistulae. [ 9 ] Moreover, we did not apply mechanical abrasion or submucosal injection because we feared that those procedures might deteriorate the fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, endoscopic treatments of gastrointestinal leaks and fistulas, including endoclipping, stent placement, application of tissue sealants and suturing devices, have been developed, and the effectiveness of such procedures has been reported 1 . Although the most common tissue sealants in clinical use are fibrin glue (FG) and cyanoacrylate 1 2 , endoscopic closure using polyglycolic acid (PGA) sheets with FG have been attempted because of the harmless nature of these sheets and the satisfactory results achieved in various surgical fields 3 4 5 6 7 8 9 .…”
Section: Introductionmentioning
confidence: 99%
“…PGA sheets are delivered with biopsy forceps and stuffed into the fistula using a tapered catheter or closed biopsy forceps 4 5 6 7 . This procedure should be repeated several times to prevent mesh dislocation, but it can be technically difficult to apply the sheets, and blindly inserting such pushing devices can injure the fistula.…”
Section: Introductionmentioning
confidence: 99%